Knowledge, attitudes and perceptions of secondary school going girls towards implanon contraceptive at Bokamoso Secondary School, Polokwane District Municipality, Limpopo Province, South Africa - Mkansi, Mantsi Annah (My University, 2018)
Background: Contraception is the pillar in reducing teenage pregnancy. Birth control methods are aimed at improving the lives of women and young girls; through minimising unplanned pregnancies and subsequent termination of pregnancy. Teenage pregnancy is a major public health problem worldwide therefore the purpose of the study was to determine knowledge, perceptions and attitudes of secondary school going girls towards implanon contraceptive. Methodology: The current study was conducted using quantitative study approach and cross-sectional study design. Data collection was done using self-administered questionnaire and data analysis was done using SPSS version 24.0. A total of 404 school going girls from grade 8-11 participated in the study. Results: The findings of the study showed that majority of participants in the study were from rural area and are black. Nearly quarter of the school girls had menarche between the ages of 12-14 and third of them received health reproductive education from school and parents. Prevalence of teenage pregnancy among study participants was low. Participants had low knowledge, displayed positive attitude and positive perception towards implanon method of contraception. Discussions: Low knowledge on what an implanon is, how it works and its side effects can serve as a barrier to its usage among teenagers. The common contributory factor to discontinuation and non-use of implanon is fear of side effects. The participants viewed implanon as effective and reliable. Conclusion: School going girls had insufficient knowledge on implanon, which may lead to non-use and early termination in the use of the method. Participants displayed positive attitude and positive perception towards implanon indicating that proper health education can increase uptake among adolescent girls. Recommendations: Provision of adolescents and youth friendly services in public health facilities can contribute to school going girls accessing implanon contraceptive method. Health education on the implanon should be strengthened by health care providers, school programs and educators to empower them and to increase the uptake of implanon.
Thesis ( MPH.) -- University of Limpopo, 2018
Keywords: School going girls; Knowledge; Attitude; Perception; Implanon contraceptive; Public health--South Africa.; Contraceptives; Public opinion.; Schoolgirls.; Teenage pregnancy